2013
DOI: 10.1002/pola.26935
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization kinetics of phosphonic acids and esters using an iodonium initiator

Abstract: Phosphonic acids are known to be useful monomers in dental restorative materials because of their good potential to provide enhanced adhesion to hydroxyapatite and their high hydrolytic stability. In this study, the photopolymerization of phosphonic acid-based monomer via the camphorquinone (CQ)/ethyl-4-(dimethylaminobenzoate) (EDAB) photoredox system is compared with a ternary system composed of iodonium hexafluorophosphate and CQ/EDAB. Photocalorimetry shows that the ternary system does not provide a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…It should be noted that the impact of the iodonium salt on the polymerization reaction depends on the type of monomers present in the system. It was found that the iodonium salt failed to enhance the photopolymerization in the presence of methacrylate phosphonic acid monomers . From the range of intensities studied here, the appropriate light intensity to obtain substantial DC with good polymerization efficiency for hydrophilic 2PI resin is in the range 229−679 mW/cm 2 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It should be noted that the impact of the iodonium salt on the polymerization reaction depends on the type of monomers present in the system. It was found that the iodonium salt failed to enhance the photopolymerization in the presence of methacrylate phosphonic acid monomers . From the range of intensities studied here, the appropriate light intensity to obtain substantial DC with good polymerization efficiency for hydrophilic 2PI resin is in the range 229−679 mW/cm 2 .…”
Section: Discussionmentioning
confidence: 82%
“…It was found that the iodonium salt failed to enhance the photopolymerization in the presence of methacrylate phosphonic acid monomers. 37 From the range of intensities studied here, the appropriate light intensity to obtain substantial DC with good polymerization efficiency for hydrophilic 2PI resin is in the range 2292679 mW/cm 2 . Both the hydrophobic resins and hydrophilic 3PI resin yield substantial DC with good efficiency at all of the light intensities studied here.…”
Section: Discussionmentioning
confidence: 94%
“…This assumption is supported by the findings of Besse et al . which reported that the addition of phosphonic acids enhances the rate of homopolymerization of acryl monomers …”
Section: Resultsmentioning
confidence: 99%
“…Another study by Besse et al showed that the addition of iodonium salt does not always result in higher polymerization efficiency. For example, in the case of methacrylate phosphonic acids, the iodonium salt had a reverse effect [17]. …”
Section: Introductionmentioning
confidence: 99%